Unveiling the impact of lipid metabolism on triple-negative breast cancer growth and treatment options - Cai, Xin-xian; Zhang, Zhe-zhong; Yang, Xiao-xiao; Shen, Wen-rui; Yuan, Liu-wei; Ding, Xi; Yu, Ying; Cai, Wen-yu (Frontiers in Oncology, 2025)
Triple-negative breast cancer (TNBC) is a subtype of breast cancer associated with poor prognosis and limited targeted treatment options. Lipid metabolism plays a pivotal role in the initiation, progression, and metastasis of TNBC by supporting cancer cell energy production, facilitating membrane biosynthesis, and regulating signal transduction. Dysregulation of lipid metabolism promotes tumor cell proliferation and contributes to processes such as epithelial-mesenchymal transition (EMT), angiogenesis, and immune evasion. Targeting lipid metabolism—such as inhibiting fatty acid synthase (FASN) and lipid metabolic byproducts—has emerged as a promising therapeutic strategy. The integration of multi-omics approaches and advanced imaging technologies can further elucidate the interactions between lipid metabolism and the tumor microenvironment, thereby supporting precision oncology. Future research should explore the role of lipid metabolism in distinct TNBC subtypes, optimize therapeutic strategies, and improve patient outcomes, particularly for those who are unresponsive to conventional treatments.